2nd Edition MSQH Guide - Ali, Norsiah binti (International Journal of Human and Health Sciences (IJHHS), 2025)
The Malaysian Society for Quality in Health (MSQH) was established in 1997 with the vision of advocating continuous quality improvement and safety in the healthcare sector. One of the key strategies utilized is accreditation. Accreditation is a self-assessment and external peer review process used by healthcare organizations to accurately assess their level of performance in relation to established standards and to implement strategies for the continuous improvement of healthcare systems. To date, the MSQH conducts four main accreditation programs: the Hospital Accreditation Programme, the Medical Clinic Accreditation Programme, the Chronic Dialysis Treatment Accreditation Programme, and the Dental Clinic Accreditation Programme. The Medical Clinic Accreditation Programme was first published in 2011, with the second edition completed in March 2024. This comprehensive document is designed to elevate the quality and safety of healthcare services provided by medical clinics in Malaysia. Building upon the foundation of the first edition, the second edition introduces significant enhancements and refinements to align with global best practices and the evolving healthcare landscape. The standard encompasses a range of critical areas, including governance, clinical operations, patient safety, infection control, and the continuous improvement of healthcare delivery systems. It emphasizes a patient-centric approach, ensuring that the services provided by clinics are not only effective but also compassionate and tailored to individual needs. The document includes detailed information on the accreditation application process, survey methodology, criteria for accreditation awards, maintenance of accreditation status, and the appeal mechanism. By establishing clear benchmarks, the MSQH Medical Clinic Standard 2nd Edition guides clinics in achieving higher levels of operational efficiency, risk management, and service excellence. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S11